Accessibility of Public and Private Amenities for people with disabilities in the Central Business District of Harare - Munemo, Emmanuel (Advances in Social Sciences Research Journal, 2018)
The study set out to determine the accessibility of public and private amenities for people with disabilities in the central business district of Harare. People with disabilities like everyone else also needed to access various amenities and services in the city. A quick look in the city seems to suggest that access to many buildings, appears to favour the able bodied at the expense of people with disabilities. Some buildings appear to have “cosmetic” adaptations in a bid to accommodate people with disabilities. This study was informed by the quantitative paradigm. The descriptive design was chosen in line with the quantitative paradigm. Random sampling was employed. Data was collected through questionnaires . The study established that many buildings in the city were not user friendly to people with disabilities. Most buildings had stairs, but no rumps, most doors could not fit wheelchairs. Inside elevators, buttons were too high for some people using wheelchairs or those of a short stature. Toilet entrances were too narrow and not disability friendly. Crossing roads at robot controlled intersections was extremely difficult for people with disabilities. The study recommended that adaptations be made to public buildings and space by putting rumps, widening entrances, having sound robots and making pavements more user friendly. The streets also needed to be decongested through harmonizing vending activities that are not orderly. Parking of vehicles also needs to be regulated to avoid the current disorderly manner in which combi drivers especially park anyhow. In view of the recent cholera outbreak stringent measures need to be put in place to provide clean water to citizens including people with disabilities.